Optimalisasi UMKM Berbasis Digital melalui Program KKN di Desa Iker-Iker Geger - Hafidz Rizky Rojabi, Muhammad; Jamal Kubro, Muhammad; Afaliyah Dikna Zahra, Astrid; Anzalina Putri, Vera; Sukaris (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This Community Service Program (KKN) aims to improve the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Iker-Iker Geger Village through digitalization, branding, and business legality. Using a participatory approach, 15 MSMEs were identified, with 2 selected for intensive mentoring. The program included Google Maps optimization, logo and banner design, packaging improvement, and assistance in NIB registration. The results show that 100% of assisted MSMEs obtained digital business locations, developed visual identities, and initiated business legalization, along with improved understanding of digitalization and branding. The program’s main contribution is a needs-based mentoring model that enhances visibility, strengthens branding, and supports business legality, although limited digital literacy remains a challenge.